2017
DOI: 10.1093/rheumatology/kex285
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations of Behçet’s disease depending on sex and age: results from Japanese nationwide registration

Abstract: We showed that clinical phenotype in early phase of BD was different depending on onset age and sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
26
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 28 publications
11
26
4
2
Order By: Relevance
“…A smoking history was present only in one 46-year-old male patient with deep vein thrombosis, indicating that there was no association of thrombosis with smoking in these patients. A Japanese and a further Turkish group have similarly reported that genital ulcers were more frequent among female patients (OR 0.29, 95% CI [0.25-0.32], p<0.001 and male 971/1138 [85.6%] vs. female 995/1095 [91.0%], p<0.001), 24,25 while this was not observed in our data. Ocular manifestations showed male predominance in both data sets; on the other hand, only the Turkish group reported male predominance of papulopustular eruptions, thrombophlebitis, and neurologic, pulmonary and vascular involvement.…”
Section: Discussioncontrasting
confidence: 53%
“…A smoking history was present only in one 46-year-old male patient with deep vein thrombosis, indicating that there was no association of thrombosis with smoking in these patients. A Japanese and a further Turkish group have similarly reported that genital ulcers were more frequent among female patients (OR 0.29, 95% CI [0.25-0.32], p<0.001 and male 971/1138 [85.6%] vs. female 995/1095 [91.0%], p<0.001), 24,25 while this was not observed in our data. Ocular manifestations showed male predominance in both data sets; on the other hand, only the Turkish group reported male predominance of papulopustular eruptions, thrombophlebitis, and neurologic, pulmonary and vascular involvement.…”
Section: Discussioncontrasting
confidence: 53%
“…The disease usually affects individuals aged between 20 and 40 years. Studies in Asia-Pacific countries have reported that 18-66% of patients have uveitis (Table 3) [47][48][49][50][51][52][53][54][55][56][57][58][59]. Interestingly, a decreasing trend in the prevalence of uveitis in Behcet's disease has been noticed in China, Japan, and Korea.…”
Section: Behcet's Diseasementioning
confidence: 99%
“…The average age of onset peaks at the second to third decades, so it generally is regarded as a disease of young adults. The clinical features and course of the disease are closely associated with gender and age [3,4]. Despite affecting almost all organs, major organ involvement rarely coexists with each other.…”
Section: Introductionmentioning
confidence: 99%